Life Long Education in Islamic Perspective - Miftahul Huda (UIN Sunan Gunung Djati Bandung, 2019)
John Dewey's one main character philosophic Pragmatism States that: the Educational process has no end beyond itself in its own end. The term statement of the concept of lifelong education began in the Western philosophic pragmatism developed there. The concept of lifelong education believes that education is not only limited to education at the school but continued up to the end of life. The concept of lifelong education appears along with the emergence of some of the challenges in the world of education as presented by Paul Lengard of which include: the rate of change, demographic expansion, innovation in science and technology, the challenge of politics, information and crisis in the pattern of life. The concept of education is apparently emerging from some Hadith of the Prophet Muhammad that encourages humans to continue to study until the end of his life. This paper tries to expose the concept of lifelong education according to the Islamic education.